Strategies Conflict between Islamic Republic of Iran and the Zionist Regime in the Caucasian Strategic Area - Hadi Ebrahimi kiapei; kamal zarei (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2020)
The South Caucasus is one of the areas where, since the end of the Cold War, and the crises caused by geopolitical and geostrategic developments, especially after the collapse of the Soviet Union, there have been rivalries and bargaining of major regional and sub-regional powers. In recent years, The presence of the Zionist regime as one of the supranational powers in the South Caucasus as the periphery of the Islamic Republic of Iran and its strategic partnership with the countries of the region, and the further expansion of the field of cooperation and strategic plans with them, has created a serious challenge to our country's vital interests. The continuation of this presence has brought about a clear opposition in various political, security, economic and cultural spheres, which, in proportion to the emergence and level of cooperation and hostilities of the states of the region, in the absence of the maintenance of the ruling states of the region could spark a conflict Cause.  The methodology of this research is based on an argumentative approach and its research methodology has a descriptive-analytic character.